Tourist Perception Towards Tourism Development: An Empirical Analysis from Nepal - Shrestha, Raj Kiran (Nepalese Journal of Hospitality and Tourism Management, 2026)
Tourism development contributes significantly to economic growth and destination sustainability. This study examines how different factors such as societal barriers, socio-cultural attractions, elementary facilities, environmental management, and destination fears influence tourist perception toward tourism development. Data were collected from 389 foreign tourists using a structured questionnaire and analyzed through reliability testing, descriptive statistics, and association and effect analysis. The findings indicate that these determinants significantly shape tourist perceptions, with infrastructure quality and environmental management playing particularly important roles. The results highlight the need for improved services, safety, and sustainable practices to enhance visitor satisfaction and long-term destination competitiveness.